Über Wissenschaft reden - Haas, Claude; Weidner, Daniel (Lingua Academica, 2019)
The volume examines the relationship between scientific self-understanding and scientific language usage in the German-speaking world around 1800. It discusses the re-founding of the university, the fraught relationship with rhetorical tradition, the presentational impact of scientific speech, and the political implications for audiences of this discourse.